2010
DOI: 10.1007/s11845-010-0644-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of platelet endothelial cell adhesion molecule-1 (PECAM-1/CD31) on pulmonary injury induced by ischemia–reperfusion in rats

Abstract: PECAM-1/CD31 is involved in the pulmonary injury induced by IR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
4
2
Order By: Relevance
“…Our results showed that Fe 3 O 4 nanozymes inhibit the excessive activation of astrocytes, reduce the damage of vascular endothelial cells, and elevate the levels of key TJ proteins including ZO-1 and Claudin-5. A previous study indicated that the expression of PECAM-1 immunoreactivity was increased by the stimulation of the proinflammatory factors after ischemia/reperfusion injury and then the expression of PECAM-1 immunoreactivity was decreased in the late stages of reperfusion . However, in our study, we found that Fe 3 O 4 nanozymes significantly elevated PECAM-1 immunoreactivity and maintained its levels during the CIS process.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Our results showed that Fe 3 O 4 nanozymes inhibit the excessive activation of astrocytes, reduce the damage of vascular endothelial cells, and elevate the levels of key TJ proteins including ZO-1 and Claudin-5. A previous study indicated that the expression of PECAM-1 immunoreactivity was increased by the stimulation of the proinflammatory factors after ischemia/reperfusion injury and then the expression of PECAM-1 immunoreactivity was decreased in the late stages of reperfusion . However, in our study, we found that Fe 3 O 4 nanozymes significantly elevated PECAM-1 immunoreactivity and maintained its levels during the CIS process.…”
Section: Discussioncontrasting
confidence: 70%
“…A previous study indicated that the expression of PECAM-1 immunoreactivity was increased by the stimulation of the proinflammatory factors after ischemia/reperfusion injury and then the expression of PECAM-1 immunoreactivity was decreased in the late stages of reperfusion. 47 However, in our study, we found that Fe 3 O 4 nanozymes significantly elevated PECAM-1 immunoreactivity and maintained its levels during the CIS process. It was reported previously that the increase of PECAM-1 enhances endothelial cell migration and restores barrier function in a wide variety of vascular permeability disorders.…”
Section: Discussioncontrasting
confidence: 66%
“…Enhanced levels of TNF-α expression have been observed following ischemia in both the brain [26,30] and cardiac tissue [28]. Serum PECAM-1 levels have been shown to be elevated following ischemia reperfusion in rats [33]. Additionally, blocking PECAM-1 attenuated neutrophil migration and accumulation in rat muscle flaps, demonstrating an overall protective effect against ischemia-reperfusion injury [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Renal IR is a process of the reduced blood supply to kidneys followed by re-oxygenation and restoration of blood flow (17). Reperfusion is critical for the recovery of renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that the onset, development and progression of ischemia-reperfusion injury are closely related to the function of different lncRNAs (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Yu et al (12) showed that, as a HIF-1α dependent lncRNA, expression level of psoriasis associated non-protein coding RNA induced by stress (PRINS) was upregulated under the prognosis of AKI (20).…”
Section: Discussionmentioning
confidence: 99%